Typology of Indonesian Stratovolcanoes: Insights from Geomorphological and Geological aspects - Indranova Suhendro; Eko Haryono (Faculty of Geography, Universitas Gadjah Mada, 2023)
This study aims to provide the first general typology of Indonesian stratovolcano (number of analyses=154), including various types of rock compositions and diverse volcanic hazards. Several parameters were evaluated, including average radius (r), average slope (S), surface roughness (RMS), rock compositions, mineralogy, and deposit characteristics. Four types were identified as follows: (1) small-least dissected cones, (2) broad-dissected cones, (3) extremely broad-dissected cones with caldera, and (4) residual-highly dissected cones. Type I is typically small (r=2.1 km), steep (S=19.8ᵒ), rough (RMS=88.8), less evolved (predominantly basic to intermediate), having abundant mafic (olivine, clinopyroxene) and minor hydrous (amphibole, biotite) minerals, with rare pumice and lava domes (mostly scoria and lava flows). Type II has moderate values of r, s, and RMS (8.8 km, 15.2ᵒ, and 47.7, respectively) with predominantly intermediate rocks, minor olivine with abundant hydrous minerals, and abundant pumice and lava domes. Type III is typically large (r=18.1 km), gentle (S=9.2ᵒ), smooth (RMS=40.1), producing abundant felsic rocks and felsic minerals (quartz and sanidine), and characterized by the occurrence of thick ignimbrite deposits. Type IV has relatively similar size to type II (r=8.2 km), but the slope is gentler with coarser surface textures (S=10.7ᵒ and RMS=56.8), includes more portion of ultrabasic rocks and mafic minerals, and has no feature of lava domes with common exposure of intrusions (e.g., dyke). We suggest that the evolution from type I to type III corresponds to maturation stage, whereas the formation of type IV represents erosional stage.